GE_GERICHTE PS/13/2020 vom 10. März 2021 - GE Cour de justice (2021)
DÉBAT DU TRIBUNAL;DROIT DE S'EXPRIMER;EXPULSION(DROIT PÉNAL);RENVOI(DROIT DES ÉTRANGERS);REPORT(DÉPLACEMENT);IMPOSSIBILITÉ | CP.66a; CP.66d